Early diagnosis is associated with improved clinical outcomes in benign esophageal perforation: an individual patient data meta-analysis - Vermeulen BD; van der Leeden B; Ali JT; Gudbjartsson T; Hermansson M; Low DE; Adler DG; Botha AJ; D'Journo XB; Eroglu A; Ferri LE; Gubler C; et al. (United States, 2025)
Background: Time of diagnosis (TOD) of benign esophageal perforation is regarded as an important risk factor for clinical outcome, although convincing evidence is lacking. The aim of this study is to assess whether time between onset of perforation and diagnosis is associated with clinical outcome in patients with iatrogenic esophageal perforation (IEP) and Boerhaave's syndrome (BS).
Methods: We searched MEDLINE, Embase and Cochrane library through June 2018 to identify studies. Authors were invited to share individual patient data and a meta-analysis was performed (PROSPERO: CRD42018093473). Patients were subdivided in early (≤ 24 h) and late (> 24 h) TOD and compared with mixed effects multivariable analysis while adjusting age, gender, location of perforation, initial treatment and center. Primary outcome was overall mortality. Secondary outcomes were length of hospital stay, re-interventions and ICU admission.
Results: Our meta-analysis included IPD of 25 studies including 576 patients with IEP and 384 with BS. In IEP, early TOD was not associated with overall mortality (8% vs. 13%, OR 2.1, 95% CI 0.8-5.1), but was associated with a 23% decrease in ICU admissions (46% vs. 69%, OR 3.0, 95% CI 1.2-7.2), a 22% decrease in re-interventions (23% vs. 45%, OR 2.8, 95% CI 1.2-6.7) and a 36% decrease in length of hospital stay (14 vs. 22 days, p < 0.001), compared with late TOD. In BS, no associations between TOD and outcomes were found. When combining IEP and BS, early TOD was associated with a 6% decrease in overall mortality (10% vs. 16%, OR 2.1, 95% CI 1.1-3.9), a 19% decrease in re-interventions (26% vs. 45%, OR 1.9, 95% CI 1.1-3.2) and a 35% decrease in mean length of hospital stay (16 vs. 22 days, p = 0.001), compared with late TOD.
Conclusions: This individual patient data meta-analysis confirms the general opinion that an early (≤ 24 h) compared to a late diagnosis (> 24 h) in benign esophageal perforations, particularly in IEP, is associated with improved clinical outcome.